Awareness about Pradhan Mantri Jan Dhan Yojana: With Reference to Mangalore City - Sudarshini; Mallika, N. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The Government of India is committed to provide financial inclusiveness and support to the marginalized and hitherto socio-economically neglected classes. Financial Inclusion is described as the method of offering banking and financial solutions and services to every individual in the society without any form of discrimination. Financial Inclusion is a national priority of the Government as it is an enabler for inclusive growth. It is important as it provides an avenue to the poor for bringing their savings into the formal financial system, an avenue to remit money to their families in villages besides taking them out of the clutches of the usurious money lenders. A key initiative towards this commitment is the Pradhan Mantri Jan Dhan Yojna (PMJDY), which is one of the biggest financial inclusion initiatives in the world. PMJDY was announced by Prime Minister, Shri Narendra Modi in his Independence Day address on 15th August 2014. An attempt has been made in this paper to study the awareness about Pradhan Mantri Jan Dhan Yojana scheme. The study is based on primary and secondary data. The primary data was gathered in the form of discussions held with respondents. The secondary data were collected from various published and non-published sources.
Keywords: Government; financial inclusion; PMJDY